Impact of Delay on Cost Overrun in Construction Projects in Algeria (European Journal of Interdisciplinary Studies, 2020)
Project success is the ultimate goal of the various project stackeholders (Salhi.R 2018). Asuccessful project means that the project is completed on time, within the agreed budget and according to the contract specifications. Delay is one of the most reccuring problems in construction project in Algeria, and it is considered as the main cause of cost overrun, time overrun, disput and claims.The objective of this paper is to mesure the impact of schedule delay on cost overrun, using the simple linear regression method and the coefficient of correlation. The proposed model can be used by practitioners as predictive mesure to address possible cost overrun.